Cairaeanthus gen. n. (Cestoda, Rhinebothriidea), with the Description of Two New Species from Dasyatis pastinaca in the Black Sea and the Sea of Azov - Kornyushin, V.V.; Polyakova, T.A. (Вестник зоологии, 2012)
Two new species were identified among cestodes collected from Dasyatis pastinaca (Linnaeus, 1758) in the Black Sea and the Sea of Azov. Their morphology corresponds in the most characters to the descriptions of Phyllobothrium lactuca van Beneden, 1850 and P. gracilis Wedl, 1855 by L. Borcea (Borcea, 1934) and T. P. Pogorel’tseva (Pogorel’tseva, 1960) from the same host and seas. В сборах цестод от Dasyatis pastinaca (Linnaeus, 1758) из Черного и Азовского морей идентифицировано два вида цестод, которые по большинству морфологических признаков соответствуют описаниям Phyllobothrium lactuca van Beneden, 1850 и P. gracilis Wedl, 1855 в публикациях Л. Борче (Borcea, 1934) и Т. П. Погорельцевой (1960) по материалам, собранным от этого же хозяина и в этом районе.